The bankers who knew too much ([Mumbai] : Miditech Pvt.Ltd., 2010)
In the monsoons of July, 1983, the body of a young male is discovered with a towelling cord around his neck, in the overgrown plantations of Hong Kong's New Territories. The ID on the dead man is Jalil Ibrahim, a young banker with from Malaysia on a business trip to Hong Kong. As the Police study his correspondence, they begin to suspect that Jalil may have discovered fatal secrets . Revisiting the case 27 years later, The Banker who knew too much tells a tale of lies, deceit, fraud and cold-blooded murder set against the backdrop of one of Hong Kong's biggest bank scandals.
DVD format
Title from title screen.
5th September 2012, Wednesday @ 9 pm on Crime and Investigation Network (Astro Channel 732).
Produced by Miditech Pvt. Ltd. for CI ASIA (2010).
Excecutive producer, Niret Alva and Nikhil J Alva.
DVD
Keywords: Jalil Ibrahim; Criminal investigation -- Homiside; Homicide investigation -- Hong Kong -- Murder